Non-invasive myocardial workiIndices derived from left ventricular pressure-strain loops in predicting the response to cardiac resynchronization therapy. (25th November 2020) - Zhu, M.R; Shu, X; Chen, H.Y; Wang, Y.N; Cheng, Y.F; Su, Y.G; Ge, J.B
Abstract: Background: Non-invasive left ventricular (LV) pressure-strain loops (PSLs) which generated by combining LV longitudinal strain with brachial artery blood pressure, provide a novel method of quantifying global and segmental myocardial work (MW) indices with potential advantages over conventional echocardiographic strain which is load-dependent. The method has been introduced in echocardiographic software recently, making MW calculations more effectively and rapidly. The aim was to evaluate the role of non-invasive MW indices derived from LV PSLs in the prediction of cardiac resynchronization therapy (CRT) response. Methods: 106 heart failure (HF) patients scheduled for CRT were included for MW analysis. Global and segmental (septal and lateral at the mid-ventricular level) MW indices were accessed before CRT. Response to CRT was defined as ≥15% reduction in LV end-systolic volume at 6-month follow-up in comparison with baseline value. Results: CRT response was observed in 78 (74%) patients. At baseline, global work index (GWI) and global constructive work (GCW) were significant higher in CRT responders than in non-responders (both P<0.05). Besides, responders exhibited a significantly higher Mid Lateral MW and Mid Lateral constructive work (CW) (both P<0.001) but a significantly lower Mid Septal MW and Mid Septal myocardial work efficiency (MWE), as well as a significantly higher Mid Septal wasted work (WW) than non-responders (all P<0.01). Baseline Mid Septal MWE (OR 0.975, 95% CI 0.959–0.990, P=0.002) and Mid Lateral MW (OR 1.003, 95% CI 1.002–1.004, P<0.001) were identified as independent predictors of CRT response in multivariate regression analysis. Mid Septal MWE ≤42% combined with Mid Lateral MW ≥740 mm Hg% predicted CRT response with the optimal sensitivity of 79% and specificity of 82% (AUC = 0.830, P<0.001). Conclusion: Mid Septal MWE and Mid Lateral MW can successfully predict response to CRT, and their combination can further improve the prediction accuracy. Assessment of MW indices before CRT could identify the marked misbalance in LV myocardial work distribution and has the potential to be widely used as a reliable complementary tool for guiding patient selection in clinical practice. Funding Acknowledgement: Type of funding source: None